Do patients with chronic neck pain have distorted body image and tactile dysfunction?. (2nd October 2017) - Moreira, Carlos; Bassi, Ana Rita; Brandão, Maria Piedade; Silva, Anabela G.
Abstract: Purpose: The aim of this study is to compare perceived neck image and tactile acuity between individuals with and without chronic idiopathic neck pain. Materials and methods: Perceived neck image was assessed in seven participants with chronic idiopathic neck pain and seven asymptomatic participants through participants' drawings. Tactile perception threshold (TPT) and two-point discrimination threshold (TPD) were also assessed using Semmes–Weinstein filaments and a mechanical calliper, respectively. Results: Participants with neck pain tended to draw their neck/shoulders less symmetrically, shorter or larger than asymptomatic participants. Despite an increased overall mean for TPD in the neck pain group, no statistically significant differences were found between groups for tactile acuity (TPD: neck pain = 21.29 ± 14.21 mm, asymptomatic = 16.43 ± 16.84 mm, p > .05; TPD: neck pain = 0.17 ± 0.08 g, asymptomatic = 0.23 ± 0.17 g, p > .05). Conclusions: The results suggest that patients with idiopathic neck pain might have a distorted image of their neck. These findings need to be further investigated in future studies with larger sample sizes.